The Effect of Digital Marketing and Knowledge Management on the Marketing Sustainability of MSMEs in Indonesia - Atika Atika (The Eastasouth Management and Business, 2023)
This research explores the impact of Digital Marketing and Knowledge Management on the Marketing Sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Through empirical analysis, the study reveals significant and positive relationships between both Digital Marketing and Knowledge Management and Marketing Sustainability. The findings underscore the critical role of digital strategies and knowledge-sharing practices in enhancing MSMEs' market presence, customer engagement, and overall marketing sustainability. Practical implications for MSMEs include the integration of these strategies into their operations and investment in training. As Indonesian MSMEs navigate an increasingly competitive business landscape, this research provides actionable insights to promote their long-term success and resilience.